Occupational stress among critical care nurses: A comparative study of public and private sector - Zahra Chegini (Wolters Kluwer Medknow Publications, 2019)
Background: Occupational stress, and the unfavorable consequences associated with it, is something frequently experienced by nurses. Materials and Methods: This cross-sectional study comparing occupational stress experienced in public and private hospitals was conducted in Iran during 2017 and involved 203 critical care nurses. Data were obtained through a self-administered questionnaire and was analyzed using an independent sample t-test. Results: The overall mean (SD) score of occupational stress experienced by critical care nurses in public hospitals was greater than that experienced in private hospitals; 3.65 (0.77) vs. 3.18 (0.94). This difference was statistically significant (t = 3.77, p < 0.001). Among the five dimensions of occupational stress, the highest mean (SD) scores in both public and private hospitals related to organizational policies, the respective scored was 3.66 (0.94) and 3.34 (1.18). Conclusions: Hospital managers, especially those in public hospitals, should review existing organizational policies and improve the workplace environment in order to decrease occupational stress.